Development and Standardization of the Gratitude Scale - Mohammad Anas Anas; Akbar Husain; Shah Mohd Khan; Asiya Aijaz (Universitas Ahmad Dahlan, 2016)
Abstract The Gratitude Scale (GS) developed by the authors was administered to 456 adults to determine the psychometric characteristics i.e. reliability and validity. Cronbach’s Alpha of the scale was found 0.91. Content validity of the scale was verified by some experts, academicians, and professionals. For testing multicollinearity and singularity ‘Determinant’ of the R-matrix was estimated and it was greater than 0.00001. The items having factor loading greater than or equal to 0.40 were selected. Total 26 items with five dimensions emerged through Exploratory Factor Analysis explaining 58.14% of the variance, which provided the evidence of factorial/construct validity of the scale. The scale can be used for research and human resource development programs in school/university and organizations. Keywords: Gratitude, content validity, Factor analysis, Multicollinearity, R-matrix